Maternal and neonatal services in Ethiopia: Measuring and improving quality - Maureen E. Canavan; Marie A. Brault; Dawit Tatek; Daniel Burssa; Ayele Teshome; Erika Linnander; Elizabeth H. Bradley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Problem: Maternal and neonatal mortality remains high in low- and middle-income countries, with poor quality of intrapartum care as a barrier to further progress. Approach: We developed and tested a method of measuring the quality of maternal and neonatal care that could be embedded in a larger national performance management initiative. The tool used direct observations and medical record reviews to score quality in nine domains of intrapartum care. We piloted and evaluated the tool in visits to the 18 lead hospitals that have responsibility to promote and coordinate quality improvement efforts within a hospital cluster in Ethiopia. Between baseline and follow-up assessments, staff from a national quality collaborative alliance provided hospital-based training on labour and delivery services. Local setting: Ethiopia has invested in hospital quality improvement for more than a decade and this tool was integrated into existing quality improvement mechanisms within lead hospitals, with the potential for scale-up to all government hospitals. Relevant changes: Significant improvements in quality of intrapartum care were detected from baseline (June-July 2015) to follow-up (February-March 2016) in targeted hospitals. The overall mean quality score rose from 65.6 (standard deviation, SD: 10.5) to 91.2 (SD: 12.4) out of 110 items (P < 0.001). Lessons learnt: The method was feasible, requiring a total of 3 days and two to three trained data collectors per hospital visit. It produced data that detected substantial changes made during 8 months of national hospital quality improvement efforts. With additional replication studies, this tool may be useful in other low- and middle-income countries.
Keywords: 330; Ethiopia; hospital quality; intrapartum care; labour services; maternal mortality; neonatal mortality